THE PROBABILISTIC STRUCTURAL INTEGRITY ASSESSMENT OF REACTOR PRESSURE VESSELS UNDER PRESSURIZED THERMAL SHOCK LOADING - WANG RongShan; CHEN MingYa; LU Feng; ZHENG WeiDong; WANG DongHui; ZHANG YaPing; FAN Zhao (Jixie qiangdu)
The pressurized thermal shock（ PTS） event poses a potentially significant challenge to the structural integrity of the reactor pressure vessel（ RPV） during the long time operation. In most countries（ with exception of the USA）,proving RPV integrity under the PTS load is based on the deterministic fracture mechanics（ DFM）. In the USA,the "screening criteria"for maximum allowable embrittlement of RPV material,which form part of the USA regulations,are based on the probabilistic fracture mechanics（ PFM）. In this paper,the FAVOR software of Oka Ridge National Laboratory is used to compare the difference between PFM and DFM analysis of the PTS even. The analysis method of FAVOR is shown through case study of the benchmark transient in the IAEA-TECDOC-1627 report. Finally,the limit of the current FAVOR（ Version6. 1） is shown.